2020
DOI: 10.1136/ijgc-2019-000937
|View full text |Cite
|
Sign up to set email alerts
|

Standard ultra-staging compared to one-step nucleic acid amplification for the detection of sentinel lymph node metastasis in endometrial cancer patients: a retrospective cohort comparison

Abstract: IntroductionThe objective of this study was to compared standard ultra-staging (SU) with one-step nucleic acid amplification (OSNA) for the detection of sentinel lymph node (SLN) metastasis in women with apparent uterine-confined endometrial cancer.MethodsAll women underwent SLN identification with complete surgical staging. All SLNs were cut perpendicular to the long axis and two adjacent 5 µm sections were cut at each of two levels 50 µm apart. At each level, one slide was stained with hematoxylin and eosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…It is a molecular-based method for the detection of metastatic lymph nodes in breast cancer or colorectal cancer patients using CK19 as a single marker. Mounting evidence has demonstrated good sensitivity and specificity of OSNA in identifying positive nodes, especially micro-metastasis, in endometrial cancer (147)(148)(149)(150). Compared with ultra-staging, OSNA is much faster thus can be done intraoperatively; moreover, it identified more SLN involvement, resulting in 20.69% of patients upstaged as FIGO stage III (150).…”
Section: Controversial Issues Pathological Ultra-staging and Lvmdmentioning
confidence: 99%
“…It is a molecular-based method for the detection of metastatic lymph nodes in breast cancer or colorectal cancer patients using CK19 as a single marker. Mounting evidence has demonstrated good sensitivity and specificity of OSNA in identifying positive nodes, especially micro-metastasis, in endometrial cancer (147)(148)(149)(150). Compared with ultra-staging, OSNA is much faster thus can be done intraoperatively; moreover, it identified more SLN involvement, resulting in 20.69% of patients upstaged as FIGO stage III (150).…”
Section: Controversial Issues Pathological Ultra-staging and Lvmdmentioning
confidence: 99%
“…Currently, the majority of investigations of molecular biomarkers of endometrial cancer SLNs are limited to a one-step nucleic acid amplification (OSNA) assay to detect known cancer-related proteins, such as CK19. 4 The current investigation provides the first global proteomic view of endometrial cancer SLNs and validates their clinical significance. In addition, the authors have applied a pioneering technology, termed “spatially resolved proteomics,” to globally characterize the proteome of endometrial cancer SLNs with different pathological grades.…”
Section: Main Textmentioning
confidence: 59%
“…There is considerable variation between institutions with respect to the number of sections examined by routine Hematoxylin and Eosin (H&E) staining, depth of sectioning into tissue blocks, the interval of microns between parallel sections and the use of immunohistochemistry (IHC) to identify tumor cells not noted on H&E stain alone [ 43 ]. Some centers have adopted one-step nucleic acid amplification (OSNA) in evaluation of SLNs and showed that patients with metastatic non-SLNs had macrometastasis in the positive SLNs as defined by OSNA [ 44 , 45 ]. OSNA could potentially replace intraoperative frozen section of SLNs in cases where the status of metastatic vs. non-metastatic SLN would influence intraoperative management.…”
Section: The Sentinel Lymph Node Conceptmentioning
confidence: 99%